Poczucie bezpieczeństwa młodych zielonogórzan = Sense of security of young people in Zielona Góra - Miłkowska, Grażyna; Papiór, Elżbieta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
A sense of security is a basic mental need of a human, indispensable for the proper development and psychosocial functioning in the completion of life tasks. The article presents the research on the subjective sense of security run on 2616 students of Zielona Góra primary schools, junior high schools and secondary schools. In the analysis the authors use a classification tree tool allowing one to identify the factors differentiating the sense of security among the youth.
Keywords: Zielona Góra (woj. lubuskie) - szkolnictwo i oświata - 21 w.; poczucie bezpieczeństwa; dzieci i młodzież szkolna; badania ankietowe; badania sondażowe